Here comes the strikeout - Kessler, Leonard, P. (New York : HarperTrophy, 1992)
Bobby changes from an"easy out" to a game-winning hitter with the help of a friend and a lot of hard work.
140
Accelerated Reader AR
Keywords: Baseball -- Fiction